Statistical mechanics - Huang, Kerson (New Delhi: Wiley-India, 1987)
Unlike most other texts on the subject, this clear, concise introduction to the theory of microscopic bodies treats the modern theory of critical phenomena. Provides up-to-date coverage of recent major advances, including a self-contained description of thermodynamics and the classical kinetic theory of gases, interesting applications such as superfluids and the quantum Hall effect, several current research applications, The last three chapters are devoted to the Landau-Wilson approach to critical phenomena. Many new problems and illustrations have been added to this edition.
Appendix A1-A4, 468-486p.; Index 487-493p.
Keywords: Statistical mechanics; Physics